Olam posted a request for proposals on Food Loss and Waste (FLW) reduction - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Based on presentations to and discussions with Olam, they posted a request for proposal and approached WUR directly on developing a methodological toolkit to assess and mitigate the post-harvest losses in their value chains. In personal communications they stress that the methodology should also address GHG emissions mitigation. This is aiming at extending the ACE calculator with a dedicated methodology for all their crops.